Unconscious deception detection measured by finger skin temperature and indirect veracity judgments—results of a registered report - van ’t Veer, Anna E.; Gallucci, Marcello; Stel, Mariëlle; Beest, Ilja van (Frontiers in Psychology, 2015)
A pre-registered experiment was conducted to examine psychophysiological responses to being lied to. Bridging research on social cognition and deception detection, we hypothesized that observing a liar compared to a truth-teller would decrease finger skin temperature of observers. Participants first watched two targets while not forewarned that they would later be asked to judge (direct and indirect) veracity, and then watched another two targets while forewarned about this. During both these phases finger skin temperature was measured. Findings pertaining to temperature partly confirmed our main hypothesis. When participants were observing a liar, irrespective of being forewarned, on average finger skin temperature declined over time. In the forewarned phase, temperature trajectories of truth-tellers were higher than those of liars, however, in the not forewarned phase, this pattern was reversed. Results confirmed our further hypotheses that participants judge liars as less likeable and less trustworthy than truth-tellers—an indication of indirect deception detection. Our hypothesis that the effect size for trustworthiness would be bigger than that of liking was not supported by the data. Additionally, and also confirming our hypothesis, participants performed around chance level when directly judging whether the target person was lying. Exploratory analyses are reported with regard to truth bias and dependency between direct and indirect veracity judgments. Limitations and directions for future work related to the existence of psychophysiological indicators of deception detection are discussed.